Type of Rockslide along the Ponorogo – Pacitan Roads, East Java, Indonesia - Arief Rachmansyah; Faridha Aprilia (Himpunan Ahli Teknik Tanah Indonesia, 2023)
The Pacitan Regency, located in the southwestern part of East Java Province, is one of the areas with low economic growth. Difficult accessibility is one of the reasons for the slow development of this region. To reaching the Pacitan Regency it can take through the Ponorogo – Slahung – Arjosari - Pacitan roads. Based on the geological condition most of roads are built on geologic formations composed of Oligocene - Miocene volcanic and intrusive rocks. Mass movement often occurs along roads and disturbs the transportation of goods and people. This paper discusses the types and mechanisms of slope failure along roads. Recognizing these two aspects of slope failure plays important role to treat them. The field survey identified 13 landslide zones with a 50–200 m bright. Based on rock type, weathering and alteration levels, and geological structure, slope failure can be classified into three types. First, the wedge rockslide occurred on the low-altered dacitic lapilli tuff. The planar – toppling type of rockslide occurred in the residual soil of the andesitic basalt lava with columnar and sheeting joint. Third, complex circular debris slides occur in highly jointed and altered dacitic intrusive rocks, which contain a large amount of clayey material. The third slide type that occurred at km 226 requires further research with an interdisciplinary approach because of moving the 200-meter-long road mass.